Dielectric, ferroelectric, piezoelectric properties, and impedance spectroscopy of (Ba0.85Ca0.15)(Ti0.9 Zr0.1)O3-x% (K0.5Bi0.5)TiO3 lead-free ceramics. (26th October 2019) - Zidi, Naima; Chaouchi, Ahcene; Rguiti, Mohamed; Lorgouilloux, Yannick; Courtois, Christian
Abstract: The influence of (K0.5 Bi0.5 )TiO3 on structure, microstructure and piezoelectric properties of (Ba0.85 Ca0.15 )(Ti0.9 Zr0.1 )O3 (BCTZ) piezoelectric ceramics was investigated. Impedance spectroscopy was used to get better understanding of the electrical properties of the materials as a function of temperature and frequency. The XRD results indicate the presence of the morphotropic phase in the BCTZ–xKBT system. Dielectric and complex impedance spectroscopic studies were carried out over wide frequency (i.e. 10 2 –10 6 Hz) and temperature (30–500 °C) ranges. The diffuseness of the dielectric peak was found to increase with increasing KBT proportion. The nature of frequency dependence of AC conductivity of BCTZ-KBT follows the Jonscher power law and calculated DC conductivity follows Arrhenius behavior. The Nyquist plots suggest the contribution of grains and grain boundaries to the electrical behavior of the materials. The ceramic with x = 0.25 mol% KBT demonstrates good properties: d 33 = 226 PC/N, T c = 110 °C, k p = 27.85%, ε r =10, 566, tanδ = 2.3%.